Oral manifestations in child patient with Ellis-van Creveld syndrome: case report - Lucas Fernando Oliveira Tomáz Ferraresso; Fabio Anevan Ubiski Fagundes; Mariella Padovese; Paola Singi; Cássia Cilene Dezan Garbelini; Farli Aparecida Carrilho Boer (Revista de Odontopediatria Latinoamericana, 2023)
Ellis–van Creveld syndrome is an autosomal recessive disorder characterized by a tetrad of disproportionate dwarfism, ectodermal dysplasia, postaxial polydactyly, and congenital heart malformations. In this article, we hereby present a case of a 6-year-old Brazilian boy with Ellis–van Creveld syndrome who presented with a remarkable number of classical oral and dental features and uncommon findings such as taurodontism. Clinical examination revealed multiple enamel hypoplasia, absent vestibular sulcus, alveolar serrations in the maxilla anterior region, missing teeth, conical teeth, lower canine rotation, bilateral posterior crossbite, dental caries, and a nodule. Radiographically were observed teeth agenesis, taurodontism of deciduous and permanent molars, and delayed tooth eruption. Clinical and radiographic findings may be present from birth and the pediatric dentist has a fundamental role in the early diagnosis of Ellis–van Creveld syndrome, as well as oral problems prevention, rehabilitation, and aesthetic interventions.